CHALLENGES AND PROSPECTS FOR MANAGEMENT OF ANTHRACNOSE CAUSED BY COLLETOTRICHUM SPECIES IN TROPICAL AFRICA - F. Christopher; E. R. Mbega; P. Ndakidemi; S. Nyalala (Journal of Animal and Plant Sciences, 2022)
Colletotrichum is a fungal genus comprising several pathogenic species that cause anthracnose in an array of key cash and food crops in the world's tropical, subtropical, and temperate regions. Considerable losses in various crops due to anthracnose in the African tropics have been reported despite the efforts to curb the disease. Several options are used to manage the disease in the region with little success. The challenges in managing Colletotrichum species include toxicity, high cost, inadequate farmers' knowledge of applying synthetic fungicides, variable and cross-infection nature of pathogenic species, physiological variability of pathogens, and unavailability of biological control agents to farmers in rural areas in tropical Africa. Several species of Colletotrichum are also known to develop mechanisms that allow them to counter immunity factors of the host plants. Consolidated information on the species prevalent, losses, and evaluation of the current control methods for anthracnose in the African tropics are essential for developing and adopting sustainable management strategies for anthracnose. This review discusses the key pathogenic Colletotrichum species in Africa, infection mechanisms, colonisation in several hosts, and the plant-pathogen interaction and losses due to the disease. Pathogen identification methods, disease management options, challenges, and prospects for the management of anthracnose in tropical Africa are also discussed.
Keywords: Anthracnose; pathogen; cross-infection; races; botanicals